DHEA and DHEA-S levels in posttraumatic stress disorder: A meta-analytic review. (October 2017) - van Zuiden, Mirjam; Haverkort, Sanne Q.; Tan, Zhonglin; Daams, Joost; Lok, Anja; Olff, Miranda
Highlights: DHEA and DHEA-S are secreted upon HPA-axis activation. Previous reports on basal DHEA and DHEA-S levels in PTSD seem inconsistent. We performed a meta-analytic review aggregating findings of previous studies. No overall differences between PTSD and control groups were observed. Higher DHEA levels were observed in trauma-exposed individuals. Abstract: Differences in hypothalamic-pituitary-adrenocortical (HPA) functioning between patients with posttraumatic stress disorder (PTSD) and controls are among the most consistent neurobiological findings in PTSD. HPA-axis activation results in the output of various steroid hormones including dehydroepiandrosterone (DHEA), which is then converted into dehydroepiandrosterone sulfate (DHEA-S), with anti-glucocorticoid actions among its pleiotropic effects. To investigate whether there is evidence for consistent differences in basal DHEA and DHEA-s levels between individuals with and without PTSD, we performed random-effect meta-analyses aggregating findings of previously published studies. Nine studies reporting on DHEA levels (486 participants) and 8 studies reporting on DHEA-S levels (501 participants) were included. No significant differences in DHEA or DHEA-S levels between PTSD and control groups were found. Exploratory subgroup analyses were performed to distinguish between effects of PTSD and trauma exposure. A trend for higher DHEA levels was found in PTSD patients compared to non-trauma-exposed controls (NTC) (k = 3, SMD = 1.12 95% CI −0.03–2.52, Z = 1.91, p  = 0.06). Significantly higher DHEA-S levels were observed in PTSD patients compared to NTC ( k  = 2, SMD = 0.76, 95% CI 0.38–1.13, Z = 3.94, p   <  0.001). Additionally, significantly higher DHEA levels were observed in trauma-exposed controls (TC) compared to NTC (k = 3, SMD = 0.66, 95% CI 0.33–0.99, Z = 3.88, p   <  0.001, I 2  = 86%) this suggests that trauma exposure, irrespective of further PTSD development, might increase basal DHEA and DHEA-S levels.